2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Migrant and Seasonal Agricultural Worker Protection Act (MSPA) [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The Migrant and Seasonal Agricultural Worker Protection Act (MSPA) establishes federal standards specific to farmworkers. (No other U.S. industry has a labor standard that applies solely to its workforce.) The original intent behind MSPA was to ensure that migrant and seasonal workers received information and standards on pay rates and deductions, working conditions, insured transportation, and employment activities. This is EDIS document FE407, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.